Catechol Conjugates Are In Vivo Metabolites of Salicis cortex - Knuth, Susanne; Abdelsalam, Rania M.; Khayyal, Mohamed T.; Schweda, Frank; Heilmann, Jörg; Kees, Martin Georg; Mair, Georg; Kees, Frieder; Jürgenliemk, Guido (Planta Medica, 2013)
After oral administration of 100 mg/kg b. w. (235.8 µmol/kg) salicortin to Wistar rats, peak serum concentrations of 1.43 mg/L (13.0 µM) catechol were detected after 0.5 h in addition to salicylic acid by HPLC-DAD after serum processing with β-glucuronidase and sulphatase. Both metabolites could also be detected in the serum of healthy volunteers following oral administration of a willow bark extract (Salicis cortex, Salix spec., Salicaceae) corresponding to 240 mg of salicin after processing with both enzymes. In humans, the cmax (1.46 mg/L, 13.3 µM) of catechol was reached after 1.2 h. The predominant phase-II metabolite in humans and rats was catechol sulphate, determined by HPLC analysis of serum samples processed with only one kind of enzyme. Without serum processing with glucuronidase and sulphatase, no unconjugated catechol could be detected in human and animal serum samples. As catechol is described as an anti-inflammatory compound, these results may contribute to the elucidation of the mechanism of the action of willow bark extract.
Keywords: Salix; Salicaceae; catechol; salicortin; metabolism; conjugates; salicylic acid; pharmacokinetic study; in vivo